Resilience and Social Adaptation to Climate Change Impacts in Small-Scale Fisheries - Villasante, Sebastián; Macho, Gonzalo; Silva, Monalisa R. O.; Lopes, Priscila F. M.; Pita, Pablo; Simón, Andrés; Balsa, José Carlos Mariño; Olabarria, Celia; Vázquez, Elsa; Calvo, Nuria (Frontiers in Marine Science, 2022)
Small-cale fisheries are important for livelihoods, food security, jobs and income worldwide. However, they face major challenges, including the increasing effects of climate change that pose serious risks to coastal ecosystems and fishing communities. Although scientific research on climate change impacts has increased in recent years, few studies have explored the social impacts on small-scale fisheries. Using Galicia (Spain) as a case study, we investigated individual and household-level adaptive responses to climate change among fishers in three fishing guilds (Cambados, Campelo, and Redondela). Specifically, we estimated the economic vulnerability of shellfishers and assessed the diversity of social adaptive responses used to deal with climate change. Although fishers’ income strongly depends on shellfishing in all studied areas, our findings show that less fishing experience and lower engagement in fisher associations tend to increase the economic vulnerability of the fishers. The fishers’ vulnerability decreases as the size of households increases, while fishers who pay a mortgage and who live in households with fewer active members tend to be more vulnerable. The findings also show that Galician shellfishers have developed a wide range of adaptation strategies to anticipate and respond to climate change impacts, namely harvesting pricier and more abundant species, reducing household expenses and increasing social involvement in shellfishery associations. Although the adaptive strategies have helped Galician fishers to deal with climate change impacts, several threats to the sustainability of shellfisheries remain, such as a decrease in the abundance of key native shellfish species, and a high dependence on public and private aid to ensure reasonable incomes for shellfisheries. These findings are of interest and relevance to other similar small-scale fisheries around the world facing similar climate change challenges.